2019
DOI: 10.1093/hmg/ddz078
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of NRAP degradation by KLHL41 contributes to pathophysiology in nemaline myopathy

Abstract: Nemaline myopathy (NM) is the most common form of congenital myopathy that results in hypotonia and muscle weakness. This disease is clinically and genetically heterogeneous, but three recently discovered genes in NM encode for members of the Kelch family of proteins. Kelch proteins act as substrate-specific adaptors for Cullin 3 (CUL3) E3 ubiquitin ligase to regulate protein turnover through the ubiquitin-proteasome machinery. Defects in thin filament formation and/or stability are key molecular processes tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…including Nrap, Fhod3, Enah, and Flnc, as well as the non-muscle myosins Myh9 and Myh10, which have been postulated as components of "pre-myofibrils" laid down as scaffolds before mature muscle-specific myosins are assembled ( Fig. 2d) [22][23][24][25][26][27] . Multiple transcription factors were enriched in transient myonuclei, including both known drivers of skeletal muscle differentiation (Ifrd1, Nfat5, Mef2a) [28][29][30] and numerous TFs with no previous associations in muscle (Ell, Creb5, Zfp697) (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…including Nrap, Fhod3, Enah, and Flnc, as well as the non-muscle myosins Myh9 and Myh10, which have been postulated as components of "pre-myofibrils" laid down as scaffolds before mature muscle-specific myosins are assembled ( Fig. 2d) [22][23][24][25][26][27] . Multiple transcription factors were enriched in transient myonuclei, including both known drivers of skeletal muscle differentiation (Ifrd1, Nfat5, Mef2a) [28][29][30] and numerous TFs with no previous associations in muscle (Ell, Creb5, Zfp697) (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…The same changes in KLHL41 expression were found in the 3× dosage group (Additional file 1: Figure S7A). It was also recently reported that nebulin-related anchoring protein, NRAP, is associated with sarcomeric dysregulation and is regulated by KLHL41 [65]. Following Z-disk AAV treatment, CTRL TC muscles trended toward higher expression while CTRL EDL muscles experienced a significant increase in NRAP expression ( Fig.…”
Section: Alterations In Nebulin Chaperone Protein Klhl41 and Downstrementioning
confidence: 57%
“…KLHL41 was also reported to regulate nebulin-related anchoring protein, NRAP [65]. Interestingly, when this protein is removed in KLHL41-deficient muscle, the myopathy phenotypes are reversed [65]. Quantification of the expression of these two proteins found that CTRL muscles produce more of both proteins in AAV-treated muscles (Fig.…”
Section: Changes In Regulatory Proteins Associated With Nemaline Myopmentioning
confidence: 87%
See 1 more Smart Citation
“…Nebulette and nebulin are homologous in function and have similar protein structure but far more studies have been conducted on dissecting nebulin and its role in skeletal sarcomere assembly and maintenance, which is discussed in this review [22]. While no chaperones have been identified for nebulin folding, NRAP, KLHL41 (skeletal muscle-specific factor), and KLHL40 bind to nebulin and prevent the giant from aggregating or degrading [23][24][25][26]. The binding of these chaperones may result in the localization of nebulin to the Z-disc.…”
Section: Thin Filament Assembly In the Sarcomerementioning
confidence: 99%